Preparation of raw oyster shell biosorbent for removal of bromophenol blue dye in aqueous solution - Salleh, Hanis Suhaila (2018)
Dye from chemical industries had shown adverse effect to the environment. Adsorption is one of the easiet method to treat dye. Raw oyster shell as food waste were successfully prepared for the removal of the bromophenol blue dye (BPB). The effectiveness of raw oyster shell were studied using different parameter such as particle size, adsorbent dosage, initial dye concentration, contact time, pH and agitation speed. The optimum particle size were obtained at 710 µm, with optimum weighed at 1.5 g. The maximum adsorption for initial dye concentration is at 350 mg/L at contact hour of 3 and pH 8. Higher adsorption was obtained at 93.92% with the addition of parameter agitation speed at 200 rpm. The data obtained from this research were best fitted to Langmuir isotherm model.